Leadership in Islamic Education - Fadila, Afifah Intan (International Conference of Moslem Society, 2019)
Leadership is a process of someone to influence other people in a group through a communication process to achieve a determined goal or target. Islamic education is a process of educating, guiding, and shaping children's personalities in accordance with Islamic teachings to be noble. Islamic education is also taught by parents to their children from the time they were born to adulthood to equip them while in the world and in the hereafter. The basics of Islamic education are sourced from the Qur'an and Sunnah Rasul which can be developed with ijtihad. The purpose of Islamic education is to form a human who is fearful of Allah SWT, by fearing Him then having a noble attitude, personality and character. Leadership in Islamic education plays a role an important for school residents. Leadership in Islamic education influences teachers to guide, educate, and motivate their students to achieve their goals and ideals. Educational leadership will be achieved well in carrying out its duties, must emulate the noble characteristics of the prophet, that is: sidq, amanah, tabligh, fathonah. Characteristics of quality leadership in Islamic education, that is: happy to get along with others, avoid false professionalism, are good at managing change, are good at choosing people, avoid doing everything themselves, and not be afraid of failure. The right leadership model in Islamic education is the situational leadership model and spiritual leadership model.